The future of competition co-creating unique value with customers - Prahalad, C. K. (Harvard Business School Pub., 2004)
"Based on a wide range of ongoing experimentation in co-creation across many industries, The Future of Competition presents a new approach to value creation. In this framework, consumer-company interactions and personalized co-creation experiences - enabled by technical and social infrastructures - allow each consumer to co-create unique value with a network of companies and consumer communities." "Using vivid examples of companies that are discovering next practices, Prahalad and Ramaswamy discuss the key building blocks of co-creation - dialogue, access, risk assessment, and transparency (DART) - and explore how new experience technologies and social capabilities can enable robust experience environments."--Jacket.